Partnership Design: Madrasah Cooperation Strategy In Increasing Public Trust - Miftahatul Qolby; Muh Hamzah; Moch Tohet (Al-Qalam Institute, 2023)
This study aims to describe cooperation strategies in increasing public trust in Madrasah. This research method is a descriptive study, with a qualitative research approach. This research was conducted at an institution located in the Probolinggo area, namely MTs Al-Hasyimi. Informant sources were obtained from the head of the madrasa, public relations and MTs Al-Hashimi teachers, while the data collection methods used were interviews, observations and documentation. The findings of this study outline that basically the community is the main consumer who uses madrasah services. However, there are some madrassas that cannot show the qualities they possess to the public audience. This is where the role of partnership design strategies is used in an effort to collaborate with the layers of society so that strong trust grows from the community to the institution. The results showed that MTs Al-Hasyimi uses partnership design management to increase public trust in the institution, the management of partnership design is implemented by; planning, implementing cooperation strategies, controlling and evaluation. The focus of research is on how the activities intensified by Madrasah MTs Al-Hasyimi in forming relationships between the madrasah and the surrounding community in order to increase public trust